Multiple intelligences of students taking a course in integrated case Study / Norlaila Abdullah - Abdullah, Norlaila (2014)
Understanding students' cognitive and personality attributes is vital in the educational industry as students posses different and mix kinds of intelligences, personalities and behaviors in classrooms. Using Gardner (1983) model of seven intelligences encompassing linguistic, logical, musical, kinesthetic, visual, interpersonal and intrapersonal, a test was conducted on twenty-two bachelor accounting students to discover and understand their differences in learning, remembering, performing and understanding in a given case study. The resulting effect, when a lecturer understands and identifies the students' common cognitive strengths and personalities, is the lecturer will be able to design not only the teaching and learning approaches that suit the students' capabilities but also the method in which the students prefer to learn and develop their strengths and weaknesses in a more constructive manner. Additionally, the lecturer can effectively assess the students' performance in classrooms. Test results indicated that the students' intelligences and personal potentials are linguistic (29%), logical (15%), musical (14%), kinesthetic (14%), visual (14%), interpersonal (13%) and intrapersonal (15%). It can be concluded that the bachelor accounting students have mix intelligences and are capable of achieving their potentials in the accounting profession.